Significance of intraparotid node metastasis in predicting local control in primary parotid cancer. (14th December 2018) - Feng, Yanping; Liu, Fei; Cheng, Guangyan; Fang, Qigen; Niu, Xinyu; He, Wei
Abstract : Objective: To analyze the metastasis rate in intraglandular lymph nodes (IGLNs) with a focus on discussing the significance of IGLN metastasis in local control (LC) of parotid gland cancer (PGC). Methods: A total of 337 patients were enrolled. Information including age; sex; and pathologic variables such as tumor (T) stage, IGLN metastasis, and follow‐up findings was extracted and analyzed. Results: IGLN metastasis was noted in 111 (32.9%) patients. Tumor stage, pathologic nodal stage, perineural invasion, resection status, and lymphovascular invasion were significantly related to IGLN metastasis. Local recurrence was noted in 67 (19.9%) patients. IGLN metastasis was an independent predictor of LC. The 10‐year LC rate was 94% for patients without IGLN metastasis, 56% for patients with metastasis in no more than two IGLNs, and 22% for patients with metastasis in more than two IGLNs. This difference was significant ( P < 0.001). Conclusion: The IGLN metastasis rate is relatively high in PGC patients and is significantly associated with disease grade and T stage. IGLN metastasis is associated with poorer local LC, and patients with more than two metastatic nodes have the worst prognosis. Level of Evidence: 4 Laryngoscope, 129:2309–2312, 2019